Ensuring quality in career guidance: a critical review. Issue 4 (4th July 2019) - Hooley, Tristram; Rice, Suzanne
ABSTRACT: In rapidly changing employment markets, career guidance has a vital role to play in supporting people in navigating transitions between education and employment across the lifespan. In this article, the issue of quality and quality assurance in career guidance is explored. Although there is no clear agreed international understanding of what quality career guidance looks like, through a review of current approaches we identify six main areas which may be quality assured and propose a new typology of approaches to assuring quality. The article concludes with a critical consideration of the issues that quality assurance approaches in career guidance generate, highlighting the need for caution so that the pursuit of quality does not undermine the goals it seeks to achieve.